1985
DOI: 10.1172/jci111916
|View full text |Cite
|
Sign up to set email alerts
|

Administration of atrial natriuretic factor inhibits sodium-coupled transport in proximal tubules.

Abstract: The newly discovered peptides extracted from cardiac atria, atrial natriuretic factors (ANFs), when administered parenterally cause renal hemodynamic changes and natriuresis. The nephron sites and cellular mechanism accounting for profound increase in Na' excretion in response to ANFs are not yet clarified. In the present study we investigated whether synthetic ANF peptide alters the reabsorption of Na' and reabsorption of solutes cotransported with Na' in the proximal tubules of rats.Synthetic ANF peptide con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(55 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…l6 - 23 It seems, howev- er, that these results were most likely a consequence of increased tubule flow rates and filtered loads, since a direct effect of ANP on volume absorption in rabbit proximal straight and convoluted tubules in vitro has not been observed. 24 In addition, micropuncture studies during ANP infusion showed increased absolute proximal and loop solute and fluid reabsorption rates with decreases only in fractional reabsorption.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…l6 - 23 It seems, howev- er, that these results were most likely a consequence of increased tubule flow rates and filtered loads, since a direct effect of ANP on volume absorption in rabbit proximal straight and convoluted tubules in vitro has not been observed. 24 In addition, micropuncture studies during ANP infusion showed increased absolute proximal and loop solute and fluid reabsorption rates with decreases only in fractional reabsorption.…”
Section: Discussionmentioning
confidence: 98%
“…23 An additional possible mode of action is the ability of ANP to act as a potent renal vasodilator, 4 ' 6 which may serve to alter peritubular capillary physical factors and thereby promote natriuresis and diuresis. Earley and coworkers 7 implicated peritubular Starling forces as important determinants of the control of sodium and water excretion, based on studies in which infusions of vasodilators, such as acetylcholine or bradykinin, led to increments in sodium and water excretion.…”
mentioning
confidence: 99%
“…Whether atrial natriuretic peptides or atrial natriuretic factors have direct tubular effect or not is controversial. Hammond et al (1985) reported that administraiton of atrial natriuretic factor inhibits sodiumcoupled transport in proximal tubules. Burnett et al (1986) also observed that whole kidney fractional delivery of sodium from the proximal tubule as estimated by the fractional excretion of lithium was increased.…”
Section: Discussionmentioning
confidence: 99%
“…But the mechanism by which atrial extract or atrial natriuretic peptide produces a natriuresis and diuresis is still unclear. Some studies have suggested that contribution of an increase in renal blood flow (Keeler and Azzarolo 1983;Wakitani et al 1985) or glomerular filtration rate Maack et al 1984 ; Beasley and Malvin 1985;Huang et al 1985) to the natriuresis and diuresis, and others have indicated direct tubular effects (Briggs et al 1982; Sonnenberg et al 1982; Pollock and Banks 1983; Burnett et al 1984Burnett et al , 1986Hammond et al 1985).…”
mentioning
confidence: 99%
“…In addition to PKA and PKC pathways, regulation of the amount of NaPi-lla by a pathway that involves protein kinase G should also be considered. Early studies documented that part of the renal response to the atrial natriuretic factor (ANF) includes changes of Na + /P i cotransport [48]. Later, it was demonstrated that increases of cGMP concentrations induced by ANP or by nitric oxide (NO) resulted in a down-regulation of NaPi-lla [3].…”
Section: Parathyroid Hormonementioning
confidence: 99%